2000
DOI: 10.1001/archinte.160.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable States in Primary Upper-Extremity Deep Vein Thrombosis

Abstract: Hypercoagulable states appear to play a significant role in idiopathic but not in effort-related UEDVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 17 publications
5
90
0
5
Order By: Relevance
“…In a series of 25 women with idiopathic UEDVT, one had received ovarian stimulation, 3 were pregnant (all through the first two months of pregnancy), and 11 were using oral contraceptives [7]. In our series, three patients were under hormonal treatment and 1 was in the second month of pregnancy, all having spontaneous UEDVT.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In a series of 25 women with idiopathic UEDVT, one had received ovarian stimulation, 3 were pregnant (all through the first two months of pregnancy), and 11 were using oral contraceptives [7]. In our series, three patients were under hormonal treatment and 1 was in the second month of pregnancy, all having spontaneous UEDVT.…”
Section: Discussionmentioning
confidence: 66%
“…He´ron et al [7] also reported a high prevalence of hypercoagulable status in a population of patients with idiopathic UEDVT compared to those with effort-related UEDVT [42% (13/31) vs. 15% (3/20)]. Leebeek et al [21] recently found thrombophilic defects in 32% of their population with UEDVT and the most frequently found coagulation abnormality was the presence of antiphospholipid antibodies (27%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study on DVT of the upper extremity no patient with a prothrombin G20210A gene variant was identified. In the previous studies the prothrombin G20210A gene variant was not evaluated, with the exception of a subgroup of 37 patients in the study of Héron et al [15]. No prothrombin G20210A gene variant was detected in their study either.…”
Section: Discussionmentioning
confidence: 91%
“…The difference in prevalence of a hypercoagulable state in the reported studies [11,15,16,17] may in part be caused by a difference in patient population, due to a variance in selection of patients. Theoretically the number of coagulation abnormalities is expected to be higher in patients with DVTUE without other predisposing factors, so-called idiopathic or primary thrombosis.…”
Section: Discussionmentioning
confidence: 95%